2018
DOI: 10.1111/jfbc.12634
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition profiling of Tunisian 10 varieties of common dates ( Phoenix dactylifera L.) at tamar stage using LC‐ESI‐MS and antioxidant activity

Abstract: This study assessed the total polyphenol, total flavonoid, total flavonols, and condensed tannins contents were also monitored and their antioxidant properties in vitro were investigated using 2,2‐diphenyl‐1‐picrylhydrazyl radical cation, 2,2′‐azino‐bis (3‐ethylbenzothiazoline‐6‐sulfonic acid), ferric reducing antioxidant power, and β‐carotene‐linoleic acid bleaching assay for second‐grade dates (Phoenix dactylifera L.), from 10 Tunisian cultivars. The results prove that the methanolic extracts of date fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
(56 reference statements)
4
5
1
Order By: Relevance
“…CTC of fresh date paste was 101.62 mg CE/100g in our study (Table 2). Our finding partially agrees with the CTCs of Algerian (74.22-394.27 mg CE/100g), Tunisian (41.85-102.37 mg CE/100g), and Moroccan (57.56-92.14 mg CE/100g (dw)) date fruits at Tamr stage (Arem et al, 2013;Benmeddour et al, 2013;Bouhlali et al, 2016;Souli et al, 2018). Total amount of condensed tannins in date palm fruit is lower than hawthorn (920-4110 mg CE/100g) and higher than strawberry (2.93-31.55 mg CE/100g), rosehip (2.02-2.34 mg CE/100g), blackberry (14.28-16.59 mg CE/100g), and blackthorn (9.53-10.50 mg CE/100g) (Dou, Leng, Li, Zeng and Sun, 2015;Turker, Kizilkaya, Cevik and Gonuz, 2012).…”
Section: Condensed Tannin Contentsupporting
confidence: 90%
“…CTC of fresh date paste was 101.62 mg CE/100g in our study (Table 2). Our finding partially agrees with the CTCs of Algerian (74.22-394.27 mg CE/100g), Tunisian (41.85-102.37 mg CE/100g), and Moroccan (57.56-92.14 mg CE/100g (dw)) date fruits at Tamr stage (Arem et al, 2013;Benmeddour et al, 2013;Bouhlali et al, 2016;Souli et al, 2018). Total amount of condensed tannins in date palm fruit is lower than hawthorn (920-4110 mg CE/100g) and higher than strawberry (2.93-31.55 mg CE/100g), rosehip (2.02-2.34 mg CE/100g), blackberry (14.28-16.59 mg CE/100g), and blackthorn (9.53-10.50 mg CE/100g) (Dou, Leng, Li, Zeng and Sun, 2015;Turker, Kizilkaya, Cevik and Gonuz, 2012).…”
Section: Condensed Tannin Contentsupporting
confidence: 90%
“…Free radicals are the major factors responsible for causing many diseases including cardiovascular disease, cancer, neural disorders, ulcerative colitis, and atherosclerosis (Elosta, Slevin, Rahman, & Ahmed, 2017). The previous studies suggest that the intake of dietary antioxidants can protect our system from damage caused by free radicals (Souli et al, 2018). The dietary supplement of anti- 2 ) and hydrogen peroxide (H 2 O 2 ) are produced naturally in cells during cellular oxidation reactions and are the most deleterious radicals causing DNA damage and lipid membrane peroxidation .…”
Section: Antioxidant Activity and Lipid Peroxidation Inhibition Capmentioning
confidence: 99%
“…Various studies have shown the anticancer and anti‐inflammatory effects of this plant, its nephroprotective and hepatoprotective effects, as well as its protective effects against toxicity‐induced reproductive dysfunction in female/male animal models (Taleb et al., 2016 ). The LC‐ESI/MS analysis of the fruit and seed of this plant showed the presence of polyphenolic compounds (isoflavonoids and flavonoids) such as gallic acid, biochanin A‐7‐glucoside, daidzein 7‐O‐D‐glucoside, syringic acid, protocatechuic acid, protocatechuic acid, genistein, p‐hydroxybenzoic acid, proantosinidin, vanillic acid, caffeic acid, syringic acid, p‐coumaric, ferulic acid, mcoumaric acid, and o‐coumaric acid (Souli et al., 2018 ). Studies show that saponins in this plant enhance the blood flow toward the female reproductive system by releasing NO and stimulating the HPG axis (Bahmanpour et al., 2006 ).…”
Section: Resultsmentioning
confidence: 99%